Diminished levels of the soluble form of RAGE are related to poor survival in malignant melanoma. Issue 11 (14th July 2015) - Wagner, Nikolaus B.; Weide, Benjamin; Reith, Maike; Tarnanidis, Kathrin; Kehrel, Coretta; Lichtenberger, Ramtin; Pflugfelder, Annette; Herpel, Esther; Eubel, Jana; Ikenberg, Kristian; Busch, Christian; Holland‐Letz, Tim; et al.
Abstract : RAGE is a central driver of tumorigenesis by sustaining an inflammatory tumor microenvironment. This study links the soluble forms of RAGE (sRAGE and esRAGE) with clinical outcome of melanoma patients. Moreover, tissue expression of RAGE was analyzed using immunohistochemistry on two independent tissue microarrays (TMA) containing 35 or 257 primary melanomas, and 41 or 22 benign nevi, respectively. Serum concentrations of sRAGE and esRAGE were measured in 229 Stage III–IV patients using ELISA and plasma concentrations of sRAGE were analyzed in an independent second cohort with 173 samples of Stage I–IV patients. In this cohort, three well‐described SNPs in the RAGE gene were analyzed. RAGE protein expression was highly upregulated in primary melanomas compared to benign nevi in the two TMA ( p < 0.001 and p = 0.005) as well as in sun‐exposed melanomas ( p = 0.046). sRAGE and esRAGE were identified as prognostic markers for survival as diminished sRAGE ( p = 0.034) and esRAGE ( p = 0.012) serum levels correlated with poor overall survival (OS). Multivariate Cox regression analysis showed that diminished serum sRAGE was independently associated with poor survival ( p = 0.009). Moreover, diminished sRAGE was strongly associated with impaired OS in the second cohort ( p < 0.001). Multivariate Cox regression analysis including the investigated SNPs revealed an independent correlation of the two interacting promoter SNPs with impaired OS. In conclusion, the soluble forms of RAGE and variants in its genetic locus are prognostic markers for survival in melanoma patients with high risk for progression. Abstract : What's new? The aptly named RAGE protein fuels chronic inflammation. In healthy persons, however, soluble forms of RAGE (sRAGE) are abundant in the serum, where they possibly serve as decoy receptors to prevent proinflammatory signaling. Here, among stage III‐IV melanoma patients, decreased serum levels of both sRAGE and the splice variant esRAGE were correlated with poor overall survival. By comparison, RAGE protein expression was significantly elevated within primary melanoma tissue. The results suggest that RAGE signaling influences the advance of melanoma and that sRAGE and esRAGE are independent survival indicators in patients at high risk of progression.